Phylogenomic inference of the interrelationships of Lake Baikal sponges. Issue 2 (28th October 2020) - Kenny, Nathan J.; Itskovich, Valeria B.
Abstract : The endemic sponges of Lake Baikal are vital components of one of the most unique ecosystems on the planet. To date we have yet to satisfactorily resolve their systematic relationships. Their relatively slow rates of molecular change, a short branch length to the common ancestor of extant species, and very plastic morphology in some species make robust species assignment and differentiation difficult. Using recently published genomic and transcriptomic resources, a novel Swartschewskia papyracea transcriptome and a phylogenomic approach, we have reassessed relationships within the Lubomirskiidae, a family of freshwater sponges endemic to Lake Baikal. After orthology assessment, paralog pruning and data curation, a concatenated 2710 orthogroup, 463, 187 site alignment was used to infer phylogenetic interrelationships between four members of the Lubomirskiidae, several freshwater sponge species and outgroup taxa, using Bayesian and Maximum Likelihood methods. This approach conclusively answers a number of previously recalcitrant questions. It confirms the position of Swartschewskia papyracea as the sister taxon to genera Lubomirskia and Baikalospongia. It strongly supports Lubomirskia monophyly, with Baikalospongia bacillifera as the sister taxa to the two species of Lubomirskia sampled here. It also confirms the relative branching arrangement of other common freshwater taxa, including the issue of Spongillidae paraphyly. This is key for interpreting the evolution of the Spongillida as a whole, and in particular, for understanding the evolution of the still enigmatic sponges of Lake Baikal.